Kulturowa reprezentacja pajdokracji dziecięcej w dyskursie pedagogiczno-literackim na temat Króla Maciusia Janusza Korczaka - Krasuska-Betiuk, Marta (Pedagogika Społeczna Nova, 2025)
The text presents testimonies of the reception of Janusz Korczak’s most popular novel, King Matt the First (1922), on the basis of which Iwona Chmielewska prepared an original artistic project in the form of a visual story (iconotext) entitled How Hard It Is to Be a King (2018). The content of scholarly discourse on the original work and its intersemiotic translation was analysed. Testimonies of the work’s reception, recorded in publications published or produced by academics after 2000, i.e. in the 21st century, were selected. Hitherto, these two cultural texts were considered from the paedocentric, philosophical, didactic, critical or literary perspective. In the first part, the main lines of the pedagogical literary interpretation are recapitulated. Emblematic images and motifs from both works – the original novel and the picture book – are scrutinised in the article as examples of the cultural representation of the child and childhood, and more specifically, the concept of paedocracy as a symbolic representation of children’s agency and subjectivity.